Making healthcare decisions for terminally ill adults and elderly in rural Bangladesh: an application of social autopsy. (2019) - , Nurul Alam Ali; Chowdhury, Hafizur Rahman; Alam, Sayed Saidul; Ali, Taslim; Streatfield, Peter Kim; Riley, Ian Douglas; Lopez, Alan D
No abstract available